ANALISIS KINERJA KEUANGAN BANK SYARIAH DI INDONESIA - Zaman, Ainun Qomaruz (An Nuqud Journal of Islamic Economics, 2025)
This study aims to analyze the financial performance of Indonesian Sharia Banks using financial ratio analysis methods, covering profitability (ROA, ROE, BOPO), liquidity (FDR, Cash Asset Ratio), and solvency. The data used are financial reports from 2021 to 2023. The analysis results indicate that the financial performance of Indonesian Sharia Banks fluctuates, but generally remains stable and has positive growth potential. The study also discusses the impact of the merger process that occurred in 2021 on the bank's financial performance. These findings are expected to provide a comprehensive overview for stakeholders in making strategic decisions and improving the quality of Islamic banking services in Indonesia